Strategi dan tantangan pengembangan karir profesional berkelanjutan guru di era digital - Ainiyah, Nuhzatul; Nizammudin, Muhammad Rafly Syahlan; Wicaksono, Rio Danu; Trihantoyo, Syunu; Sholeh, Muhammad (Jurnal Pendidik Indonesia, 2025)
Teacher career development is a strategic aspect in improving the quality of education, especially in today's dynamic digital era. However, career development for teachers faces various challenges, such as the need to adapt to technological advancements, changes in educational policies, and increasingly complex professional competency demands. This study aims to analyze the strategies and challenges of continuous professional development (CPD) for teachers in the digital age. The method used in this research is a literature review with a qualitative descriptive approach. Data were obtained from various sources, including scientific journals, books, research reports, and academic publications. The literature was analyzed based on thematic relevance, research methodology, key findings, and provided recommendations. The results show that teacher career development through the CPD approach is crucial for enhancing teachers’ competencies in a sustainable manner. Supporting factors include training, motivation, education, digital technology, and regulatory support such as the Teacher and Lecturer Law. The challenges encountered include inefficiencies in the career development documentation system and the still low level of professionalism among some teachers. Nevertheless, the digital era also presents significant opportunities through online learning platforms, digital certification, and professional networking collaborations that can accelerate the teacher career development process.